Photoexcitation of 13C, 15N, 17O, 17F and 39K in the Framework of Particle-Core Coupling Model (PCM) - A. Radhi, R.; A. Abbas, A.; M. Abdullah, M. (University of Thi-Qar Journal of Science, 2009)
Photoexcitation of the collective low-lying states in 13C, 15N, 17O, 17F and 39K are studied in the framework of Particle-Core Coupling Model (PCM).According to PCM, the total Hamiltonian is diagonalized in the configurationmixing space of the basis states which consist of the core states that restrictedto at most three quadrupole and two octupole phonon excitations and harmonicoscillator single-particle states. The resulting eigenvalues, correspond to theenergy levels and the eigenvectors, are used to calculate the magnetic dipole moment μ(n.m.), electric quadrupole moment Q(e. fm2 ), and reduced transition probability B(M1)↓(n.m.)2 and B(E2)↓(e2 fm4 ). The core polarization effects are introduced by giving the odd nucleon an effective charge and effective g-factor to obtain the best description for data.